Antimicrobial properties of platelet-rich preparations. A systematic review of the current pre-clinical evidence. (18th May 2016) - Fabbro, Massimo Del; Bortolin, Monica; Taschieri, Silvio; Ceci, Caterina; Weinstein, Roberto L.
Abstract: In recent years autologous platelet concentrates (APCs) have become popular in several medicine fields, representing a valuable adjunct to regenerative surgical procedures. Beneficial effects in the control of postsurgical discomfort and infection have also been frequently reported, suggesting that APC may possess anti-inflammatory and antimicrobial properties. The aim of the present review was to summarize the current evidence regarding the antimicrobial effects of platelet concentrates, investigated by in vitro and animal studies. This review was conducted following a systematic approach. An electronic search was performed on MEDLINE, EMBASE and Scopus databases using appropriate search terms, without language or time restrictions. Preclinical studies assessing the antimicrobial activity of APC were included and divided according to the experimental design. Twenty in vitro studies and four animal studies, investigating APC effects on a broad range of microorganisms, were included. In in vitro studies APC reduced the growth of microorganisms during the first hours of incubation, while they could not completely break down the microbial load. In fact, over time a recovery of bacterial growth was always observed, suggesting that APCs display a bacteriostatic rather than a microbicidal activity. All animal studies showed that APC administered by local injections were able to reduce the infection caused by different microorganisms, although to a lesser extent compared to antibiotics. In conclusion, although the exact action mechanisms of interaction with microbial pathogens need further investigation, platelet concentrates proved to have antimicrobial properties, and therefore could represent a useful natural substance for controlling postoperative infections at surgical sites.